ANALYSIS OF NEW PRIMER PAIR CANDIDATES OF rbcL GENE FOR IDENTIFICATION OF MICROALGAE SCENEDESMACEAE - Megga Ratnasari Pikoli (Universitas Medan Area, 2023)
Scenedesmaceae is one of the microalgae groups that has been widely studied as promising biodiesel feedstock. Its morphological identification is often confused by environmental changes, so it requires molecular identification as well. The current study aimed to obtain primer pair candidates that identify the Scenedesmaceae based on the rbcL gene. The research used bioinformatics tools, which harvested rbcL protein sequence data, performed multiple sequence alignments, and designed primers based on conserved and less-conserved regions. The best left and right primers selected based on sequence length, melting temperature, 3' end stability, number of hairpins, and self-dimers, were paired, and three candidates were obtained. The three pairs were examined based on melting temperature difference, number of hetero-dimers, length of amplified nucleotide product, number of hits, and number of genera captured from the GenBank. Sce-16 (F, 5'-TGGTCGTGCTGTTTATGAATGT-3' and 1_RL, 5'-TGCCAAACATGAATACCACCA-3'), which is back-translated according to Hariotina sp. (AOY36008.1), is the most preferred candidate compared to the other two pairs after discussing their advantages and disadvantages. In the future, the proposed primer candidate needs to be validated through in vitro amplification with some optimizations to eliminate potential weaknesses.